Wali, Sultan, Kiai, dan Santri dalam Tadisi Agama dan Politik Islam Jawa - Chalik, Abdul (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
The article discusses the role of wali (the Muslim saints), sultan, kiai, and santri within religious tradition and politics in Java. The wali (commonly known as Walisongo or ?the Nine Saints?) were people who initially spread Islam in Java. In their efforts to develop Islam, Walisongo also equipped their pupils with religious knowledge to spread Islam in the future. This is from such process the transfer of Islamic knowledge was primarily set off. Once the transition periods began, the role of wali had subsequently vanished and replaced by the formal ruler, namely sultan. The Mataram Sultanate was the biggest Islamic sultanate ever in the history of Java. Owing to the supremacy of the Sultan, Kiai Kasan Besari?as an ample example of kiai mentioned in this article?built a pesantren in an area called tanah perdikan (a tax haven) in Tegalsari Ponorogo, East Java, which became an origin of institutionalization of the pesantren in Java. The Sultan provided the pesantren both material aids and other kinds of support, including entrusting his sons to learn religious knowledge in it. It had been also followed by the royal courtiers and the best cadres of the sultanate who subsequently became litterateurs of the Kingdom.